The Elimination of Fanleaf Virus from Grapevines Using in vitro Somatic Embryogenesis Combined with Heat Therapy - Goussard, P.G.; Wiid, J. (South African Journal of Enology and Viticulture, 2017)
Somatic embryos were successfully regenerated from callus tissue of anthers and ovaries excised from inflorescences of grapevines infected with grapevine fanleaf virus (GFLV). Production of pro-embryogenic masses (PEMS) was controlled by specific growth regulators and culture conditions, including heat incubation at 35°C. Somatic embryos (containing roots and cotyledons) and plantlets were subjected to immunosorbent electron microscopy (ISEM) and serological tests (ELISA). Results show that somatic embryogenesis in combination with heat therapy of the cultures is an effective procedure to eliminate GFLV from anther and ovary source material.